2022
DOI: 10.1371/journal.pone.0271181
|View full text |Cite
|
Sign up to set email alerts
|

Predictive significance of joint plasma fibrinogen and urinary alpha-1 microglobulin-creatinine ratio in patients with diabetic kidney disease

Abstract: Background Although many biomarkers have high diagnostic and predictive power for diabetic kidney disease (DKD), less studies were performed for the predictive assessment in DKD and its progression with combined blood and urinary biomarkers. This study aims to explore the predictive significance of joint plasma fibrinogen (FIB) concentration and urinary alpha-1 microglobulin-creatinine (α1-MG/CR) ratio in DKD. Methods A total of 234 patients with type 2 diabetes were enrolled, and their clinical and laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Urinary α1MG level is reportedly useful as a predictive marker of diabetic kidney disease 14 . The reduction in urinary α1MG level by empagliflozin has been reported 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Urinary α1MG level is reportedly useful as a predictive marker of diabetic kidney disease 14 . The reduction in urinary α1MG level by empagliflozin has been reported 15 .…”
Section: Discussionmentioning
confidence: 99%
“…However, their study did not clarify if these differences remained statistically significant after accounting for confounding variables. Pan et al [ 8 ] identified increased FIB and D-D levels in DKD patients relative to type 2 diabetics without complications. In a more detailed examination of coagulation parameters, they observed no significant association between PT, APTT, TT, and DKD, with only FIB exhibiting a significant correlation postmultiple regression analysis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of DKD is believed to be multifaceted. Numerous studies have underscored the pivotal role of abnormal coagulation, highlighting the hypercoagulable state observed in a significant proportion of DKD patients [ 8 , 9 , 21 , 22 ]. Potential contributors to this state encompass aberrant glucose and lipid metabolism, a microinflammatory milieu, oxidative stress, hypoproteinemia, hemodynamic alterations, and platelet activation in DKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation